Comparing Life Expectancy Determinants between Saudi Arabia and United Arab Emirates from 1980–2020 - Anak Agung Bagus Wirayuda; Abdulaziz Al-Mahrezi; Moon Fai Chan (European Journal of Investigation in Health, Psychology and Education, 2023)
Despite marked advancements, life expectancy (LE) growth in Saudi Arabia and the United Arab Emirates (UAE) has remained stagnant compared to other developed nations. This study aims to investigate the significant correlation between macroeconomic (ME), sociodemographic (SD), and health status and resources (HSR) factors and LE to formulate an explanatory model for Saudi Arabia and the UAE—a previously unexplored area. Utilizing an ecological, retrospective, time-series study design, we delved into secondary data on SD, ME, and HSR factors and LE of the populations of the UAE and Saudi Arabia spanning three decades (1980–2020). We employed partial least squares–structural equation modeling for statistical analysis. Our analysis revealed significant direct impacts of HSR factors on LE for Saudi Arabia (β = 0.958, p < 0.001) and the UAE (β = 0.716, p < 0.001). Furthermore, we discerned a notable indirect influence of ME factors on LE, mediated through SD and HSR factors for Saudi Arabia (β = 0.507, p < 0.001) and the UAE (β = 0.509, p < 0.001), along with a considerable indirect effect of SD factors on LE through HSR (Saudi: β = 0.529, p < 0.001; UAE: β = 0.711, p < 0.001). This study underscores the mediating role of a nexus of ME–SD–HSR factors on LE in Saudi Arabia and the UAE. Consequently, these findings signal an imperative need for holistic policy interventions addressing ME, SD, and HSR factors, aiming to alter health behaviors and improve LE projections for Saudi Arabia and the UAE in the long run.